VOLCANOSTRATIGRAPHY AND PETROGENESIS OF PENANGGUNGAN VOLCANO, MOJOKERTO AND PASURUAN DISTRICT, EAST JAVA. - FEBRI AGUS SETYAWAN, REZA
Mount Penanggungan is an inactive volcano and located in the north of East Java. The purpose of this research are to identify the geological aspects that consists geomorphology, stratigraphy, geological structure, magmatism, magma series, tectonic, and geological history using the principle of volcanostratigraphy and petrogenesis. The method used in this research are remote sensing analysis (SRTM image and topography map) petrographic analysis, and geochemistry analysis using XRF (X-Ray Fluorescence). Geomorphology of the research area is divided into six geomorphological units, which are Intrusion Hill Unit, Volcano Foothill Unit, Cone Volcano Unit, Lava Dome Unit, Volcano Hillside Unit, and Lava Flow Ridge Unit. Stratigraphy research area is divided into two Crowns (Penanggungan Crown and Welirang Crown). Penanggungan Crown consist of Bende Hummock, Belik Hummock, Sendang Hummock, Jembe Hummock, Kedungudi Hummock, Gajahmungkur Hummock, Wangi Hummock, Bekel Hummock, Kemuncup Hummock. The volcanic products of Penanggungan Crown and Welirang Crown are pyroclastic rock, andesite lava, basalt lava, and andesite intrusion. The geological structure of the research area consists of primary and secondary structures. The primary structure consists of a sheeting joint, vesicular, coherent, and an autobreccia. While the secondary structure consists a Sumbersuk strike-slip left-lateral fault (sinistral) and Watukosek strike-slip left-lateral fault (sinistral). Results from petrographic analysis and rock geochemistry show that differentiation of magma which occurred in Penanggungan Volcano consists crystal fractionation, rock assimilation and magma mixing with (High-K) Calc-Alkaline magmatic series in Island Arc's tectonic environment.